IDEOLOGI BULETIN DAKWAH AL-ISLAM DALAM KAJIAN WACANA KRITIS - Budiman, Budiman; Musyarif, Musyarif; Firman, Firman (P3M STAIN Parepare, 2016)
This study was conducted in order to understand the form and strategy used by HTI to extend the ideology in the perspective of critical analytical discourse. The method used in this study was critical discourse model of Fairclough by examining the aspect of production, such as form, strategy, argumentation background and used the critical analysis discourse by Roger Fowler, that assume the language as social practice. The discourse that was used as the object of this study was the Al-Islam bulletin available in many mosques every Friday from year 2011 through 2012, limited only for ideology related discourse. The research findings showed that the form of ideology intended to be implanted by HTI in endeavor discourse were politic and democracy ideology, economic and social ideology, and religious ideology. The strategies used by HTI reconstructing discourse are the vocabulary choice such as words classification, meaning relation and metaphor; the structure of discourse; confirmation of arguments and form with conclusion. There was an ideology used in reproduction of HTI discourse, such as al-Qurâan, prophet sunnah, and Islam short live.